A systematic literature review of risk and gender research in tourism. (February 2017) - Yang, Elaine Chiao Ling; Khoo-Lattimore, Catheryn; Arcodia, Charles
Abstract: Resonating with a growing sense of uncertainty recently, an increasing number of studies have been dedicated to travel risk because risk and tourism are intrinsically connected. However, existing tourism risk literature was criticized for lacking theoretical foundations, which has resulted in fragmented understandings, including contradictory opinions regarding the effect of gender on risk perception. In response to these criticisms, this study systematically investigates tourism risk literature from a gender perspective, with an aim to map out what is known about the gendered travel risk and what needs to be explored further. The review findings suggest that a majority of existing risk and gender studies have prioritized the experience of Western travelers. The findings indicate a lack of a gender- and risk-focused investigation and theoretical framework, and a dearth of an interpretive and reflexive approach. A plethora of evidence of gender difference in tourist risk experience has been identified. Highlights: This study provides a systematic review of risk and gender research in tourism. Existing risk and gender literature is found to be Western-dominated. A majority of existing studies have favored a positivist and quantitative method. Gender- and risk-focused research and theoretical discussion are lacking. Recommendations for future tourism research in gender and risk are provided.